2009
DOI: 10.1111/j.1745-3933.2009.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of relativistic jets from rotating, accreting black holes via fully three-dimensional magnetohydrodynamic simulations

Abstract: Rotating magnetized compact objects and their accretion discs can generate strong toroidal magnetic fields driving highly magnetized plasmas into relativistic jets. Of significant concern, however, has been that a strong toroidal field in the jet should be highly unstable to the non‐axisymmetric helical kink (screw) m= 1 mode leading to rapid disruption. In addition, a recent concern has been that the jet formation process itself may be unstable due to the accretion of non‐dipolar magnetic fields. We describe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
414
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 388 publications
(435 citation statements)
references
References 81 publications
20
414
0
1
Order By: Relevance
“…These are produced by dynamically important magnetic fields twisted by the differential rotation of the black hole's accretion disk or ergosphere (Blandford & Znajek 1977;Blandford & Payne 1982;McKinney & Blandford 2009;Zamaninasab et al 2014). Observational signatures for the existence of such helical magnetic fields can be obtained by looking for Faraday rotation gradients, produced by the systematic change in the net line-of-sight magnetic field component across the jet width (Laing 1981;Asada et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These are produced by dynamically important magnetic fields twisted by the differential rotation of the black hole's accretion disk or ergosphere (Blandford & Znajek 1977;Blandford & Payne 1982;McKinney & Blandford 2009;Zamaninasab et al 2014). Observational signatures for the existence of such helical magnetic fields can be obtained by looking for Faraday rotation gradients, produced by the systematic change in the net line-of-sight magnetic field component across the jet width (Laing 1981;Asada et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The propagation, radial structure and growth or damping of instability produced jet structures depends on whether the structure is magnetically (CDI) or kinetically (KHI) induced. Non-relativistic and relativistic simulations of magnetized jet formation and/or propagation have shown helical structures attributed to CDI, e.g., ; Nakamura et al (2001); Ouyed et al (2003); Nakamura & Meier (2004); Nakamura et al (2007); Moll et al (2008); Moll(2009);McKinney & Blandford (2009);Carey & Sovinec (2009). Non-relativistic and relativistic simulations of kinetically dominated jets have shown that helical structures may be attributed to KHI, e.g., ; Hardee et al (2001); Hardee & Hughes (2003).…”
Section: P E Hardeementioning
confidence: 99%
“…The 3D relativistic jet generation simulation performed by McKinney & Blandford (2009) indicates relatively rapid, less than 25 gravitational radii, but non-disruptive kink development over 500 gravitational radii. Our simulations for static and moving kinks suggest that the non-disruptive kink development in the jet generation simulation could be a result of the velocity shear surface located less or on order of the characteristic magnetic radius and a transverse density increase.…”
Section: Current Driven Instabilitymentioning
confidence: 99%
“…For our non-MAD model, we use the dipole model of McKinney & Blandford (2009). In this simulation, a MAD state does not develop and the accretion is driven by the magneto-rotational instability.…”
Section: Grmhd Simulationmentioning
confidence: 99%